FACTS, IDEAS AND OPEN PROBLEMS ON TRENCH-ARC-BACKARC SYSTEMS - Uyeda S. (My University, 1986)
In the framework of plate tectonics, loci of trench-arc-backarc (T-A-BA) systems are identified with those of subduction, and various features characteristic to T-A-BA systems are causally attributed to subduction. While some aspects of such features as arc seismicity, seismic wave velocity attenuation structures and trench topography are rationally explained by subduction models, two fundamental features are difficult to explain. They are (1) the thermal state represented by high heat flow and arc volcanism in arc-backarc regions and (2) the extensional opening of backarc basins. Opening of backarc basins is closely related to another very basic problem of (3) why are arcs arcuate in shape? This paper reviews facts and ideas on some of these problems. Frictional heating between subducting slab and mantle wedge above the slab is probably of little importance in generating high heat flow and magma in arc-backarc regions. Convective asthenospheric motion mechanically induced by subducting slab may play a key role as it carries hot deeper mantle materials upwards. This motion, however, would not generate shear stress strong enough to cause backarc spreading. Backarc spreading would probably be a passive process governed chiefly by plate motions, i. e. by mutual retreat of overriding plate and trench line. Sphericity of the earth, as well as collision of buoyant features, may be responsible for making subduction zones arcuate in shape, and possibly play some role in the passive backarc spreading. Departure from simple 2-D treatment is essential for better understanding of subduction, i. e. it is important to look at individual subduction zones in more detail (comparative subductology), to look into the zones where collision is occurring (Vogt effects) and to consider 3-D aspects of shell tectonics. It is noted, however, that the more our knowledge and ideas advance, the more distant we are from ultimate solutions.